Mn-ZIF nanozymes kill tumors by generating hydroxyl radical as well as reversing the tumor microenvironment - Han, Jiyu; Ma, Hairong; Ai, Songtao; Wan, Daqian (Frontiers in Pharmacology, 2024)
Tumor tissues are well known for their unique high hydrogen peroxide (H2O2) microenvironment. How to exploit this tumor microenvironment for tumor cell killing is a question. In this study, a Mn-doped metal-organic framework (Mn-ZIF) was constructed. It possesses good peroxidase (POD) activity, which can oxidize tumor-localized H2O2 into hydroxyl radicals (·OH), that possesses the ability to directly kill tumor cells. More surprisingly, in vivo experiments the researchers not only observed the tumor-killing effect of Mn-ZIF, but also found it changes in macrophage phenotype in the tumor region. There was an increase in macrophage polarization towards the M1 subtype. This suggests that the tumor-killing effect of Mn-ZIF not only comes from its POD activity, but also regulates the immune microenvironment in the tumor region. In conclusion, the preparation of Mn-ZIF provides a new way for comprehensive tumor therapy.